KARAKTERISTIK KIMIA DAN SENSORI BAKSO IKAN BAJI-BAJI (Grammoplites scaber.) DENGAN SUBSTITUSI JAMUR TIRAM PUTIH (Pleurotus ostreatus). CHEMICAL AND SENSORY CHARACTERISTICS OF BAJI-BAJI FISH MEATBALLS (Grammoplites scaber.) WITH SUBSTITUTION WHITE OYSTER MUSHROOM (Pleurotus ostreatus) - Paramestia Andani; Erdi Suroso; Susilawati Susilawati; Dyah Koesoemawardani (Jurnal Agroindustri Berkelanjutan, 2023)
The study aimed to determine the effect of white oyster mushroom substitution on the chemical and sensory characteristics of baji-baji fish meatballs and the best formulation for making baji-baji fish meatballs with white oyster mushroom substitution. The study was arranged in a Completely Randomized Block Design (CRBD) with a single factor using six levels of ratio of baji-baji fish to white oyster mushrooms, P1 (100%: 0%); P2 (90%: 10%); P3 (80%: 20%); P4 (70%: 30%); P5 (60%: 40%); P6 (50%: 50%). The research consisted of the process of preparing white oyster mushrooms, making fish meatballs, sensory testing covering parameters of colour, aroma, texture, taste, and overall acceptance and chemical testing, including water content and ash content, to get the best treatment which was then tested for protein content and crude fibre content. The data obtained were analyzed statistically using the Bartlett and Tuckey test and then continued with the ANOVA test and the 5% LSD test. The results showed that substituting white oyster mushrooms in manufacturing fish meatballs significantly affected the chemical properties of fish meatballs, including water and ash content, and sensory properties such as colour, aroma, texture, taste and overall acceptance. The best treatment was P2 (90% baji-baji fish and 10% white oyster mushroom) with sensory characteristics of white colour, distinctive fish aroma, very chewy texture, taste and overall acceptance of liking, water content 67.07%, ash content 2.12 %, the protein content of 11.07% and crude fibre content of 2.21% and are following Indonesian National Standard of fish meatballs (SNI 7266:2017).